The effects of combined strength and endurance training on running performance the following day - Doma, K.; Deakin, G. B. (International Journal of Sport & Health Science, 2013)
This study examined running economy (RE) during a two-stage incremental protocol that was combined into an endurance training session 6 hours following a strength training session. In addition, this study investigated running performance which consisted of a two-stage RE protocol and time to exhaustion (TTE) the day after strength and endurance training sessions undertaken on the same day. Twelve trained and moderately trained male runners performed strength and endurance training sessions 6 hours apart with running performance tests conducted the following day. Cost of running (CR) and rate of perceived exertion (RPE) were collected during the endurance training session whereas CR, RPE and TTE were collected during the running performance test. Maximal voluntary contraction (MVC) tests were conducted prior to and following the strength and endurance training sessions and the running performance tests. The results showed that CR significantly increased during the second stage of the endurance training session (p<0.05). During the running performance test, significant increases were found for CR during the first and second stages and for RPE during the second and third stages (p<0.05). The MVC was significantly reduced immediately following the strength training sessions, pre-post the endurance training session, and running performance test (p<0.05). The findings in the current study show that RE is impaired 6 hours following a strength training session. Furthermore, combined strength and endurance training on the same day appears to cause an accumulation effect of fatigue which impairs running performance the following day.